Made in Cascavel: a case study on the export of pasteurized eggs to the United Arab Emirates - Martins, Pedro Bruno Carneiro (2024)
Chicken eggs have been considered a staple food in human diet all over the world. Despite the relevance of the industry and its products, the Brazilian and international literature on the internationalization of hen egg producing companies is scarce. Given the need to provide managers with some guidelines in the complex process of internationalization, especially with regard to international market selection and international market entry strategy, it was analyzed if the company object of the present case study was ready to expand internationally based on its business model, domestic competitive landscape, resources and capabilities. After, an extensive research of the literature, together with the participation in an international food fair (ANUGA 2023) and conversations with key individuals in the sector, led to the selection of the internationalization frameworks proposed by the traditional literature that best address the reality of egg producing companies. It was concluded that the models developed by Cavusgil (1985) for international market selection and Dunning (1980) for foreign market entry strategy cover all the main strategic factors to be considered when drafting the process of internationalization. Despite the limitations faced in collecting secondary data and the number of interviews conducted, the present paper inaugurates the first steps towards the elaboration of the internationalization plan for Brazilian hen egg producers who aim to export its products.